Association between the level of partial foot amputation and gait: a scoping review with implications for the minimum impairment criteria for wheelchair tennis. (5th December 2022) - de Oliveira, Fábio Carlos Lucas; Williamson, Samuel; Ardern, Clare L; Fagher, Kristina; Heron, Neil; Janse van Rensburg, Dina Christina (Christa); Jansen, Marleen G T; Kolman, Nikki; O'Connor, Sean Richard; Saueressig, Tobias; Schoonmade, Linda; Thornton, Jane S; et al.
Abstract : Objective: This scoping review examines how different levels and types of partial foot amputation affect gait and explores how these findings may affect the minimal impairment criteria for wheelchair tennis. Methods: Four databases (PubMed, Embase, CINAHL and SPORTDiscus) were systematically searched in February 2021 for terms related to partial foot amputation and ambulation. The search was updated in February 2022. All study designs investigating gait-related outcomes in individuals with partial foot amputation were included and independently screened by two reviewers based on Arksey and O'Malley's methodological framework and reported according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for scoping reviews. Results: Twenty-nine publications with data from 252 participants with partial foot amputation in 25 studies were analysed. Toe amputations were associated with minor gait abnormalities, and great toe amputations caused loss of push-off in a forward and lateral direction. Metatarsophalangeal amputations were associated with loss of stability and decreased gait speed. Ray amputations were associated with decreased gait speed and reduced lower extremity range of motion. Transmetatarsal amputations and more proximal amputations were associated with abnormal gait, substantial loss of power generation across the ankle and impaired mobility. Conclusions: Partial foot amputation was associated with various gait changes, depending on the type of amputation. Different levels and types of foot amputation are likely to affect tennis performance. We recommend including first ray, transmetatarsal, Chopart and Lisfranc amputations in the minimum impairment criteria, excluding toe amputations (digits two to five), and we are unsure whether to include or exclude great toe, ray (two to five) and metatarsophalangeal amputations. Trial registration: The protocol of this scoping review was previously registered at the Open Science Framework Registry (https://osf.io/8gh9y ) and published.